Penguatan Kapasitas Keorganisasian pada Ikatan Remaja Masjid Al-Mukminin Kelurahan Binawidya Kota Pekanbaru - Jaya, Rony; Wahyudi, Rodi; Rafi, Mhd.; Muslim, Muslim (Edumedia Solution, 2023)
The realization of faithful, pious, and noble youth is part of the youth development goals in Law 40 of 2009 concerning youth. The Mosque Youth Association (IRMA) Al-Mukminin, Bina Widya Village, Pekanbaru City can become a pioneer and a local scale spectrum to optimize the role of youth through activities to prosper the mosque as part of an effort to realize these youth development goals. Moving on from this, community service to increase the organizational capacity of IRMA Al-Mukminin was carried out. The purpose of the activity is to strengthen the understanding and organizational capacity of IRMA Al-Mukminin. The service method uses a transformative approach through the stages to know, identify problems, develop plans, take action, and build awareness in a sustainable manner. The results of community service activities were in the form of an increase in the organizational capacity of the Al-Mukminin Mosque Youth Association (IRMA) in Binawidya Village, Pekanbaru City.